Uterine Contractions Features: Evolution Throughout Pregnancy Using Electrohysterography - Almeida, Martim Manuel Oliveira e Silva Ferreira de (2022)
Tese de mestrado, Bioestatística, Universidade de Lisboa, Faculdade de Ciências, 2022